Other mothers : beyond the maternal ideal - Rosenman, Ellen Bayuk; Klaver, Claudia C. (The Ohio State University Press, 2008)
"Other Mothers, edited by Ellen Bayuk Rosenman and Claudia C. Klaver, offers a range of essays that open a conversation about Victorian motherhood as a wide-ranging, distinctive experience and idea. In spite of its importance, however, it is one of the least-studied aspects of the Victorian era, subsumed under discussions of femininity and domesticity." "Other Mothers joins revisionist approaches to femininity that now characterize Victorian studies. Its contents trace intersections among gender, race, and class; question the power of separate spheres ideology; and insist on the context-specific nature of social roles. The fifteen essays in this volume contribute to the fields of literary criticism, history, cultural studies, and history"--Jacket